Resepsi Teks Kakawin Hariwangsa dalam Geguritan Hariwangsa - Peri Yadnyana, I Wayan; Suardiana, I Wayan; Suryati, Ni Made (Humanis; Vol 17 No 3 (2016), 2016)
This study discusses Kakawin Hariwangsa and Geguritan Hariwangsa. The purpose of research describing the structure of narrative and how far do the reception kakawin into shape geguritan. This study used structural theory of Teeuw, and reception theory of Junus powered by Jausz, Kelvin, and Fokema. Methods and techniques use divided into three stages, namely: (1) at the stage of providing data used method of reading aided engineering log and translation techniques, (2) at the stage of data analysis used descriptive comparative aided engineering analytical description, and (3) at the stage of presentation of the results of analysis Data used informal methods aided engineering inductive and deductive. The results achieved in this study, known Kakawin Hariwangsa narrative structures using a loose groove with the background of a kingdom Dwarawati, Kundina kingdom, the kingdom of the Pandavas, and setting time in the afternoon. The characters in Kakawin Hariwangsa namely Sang Krishna, Dewi Rukmini, Sang Jarasandha, Sang Pandavas and Hyang Narada. Themes in kakawin hariwangsa is loyalty and mandate that every person who faithfully and waited for her beloved then they will meet and unite with the person loves. Geguritan Hariwangsa using loose groove with background Dwarawati kingdom, the kingdom Kundina, the kingdom Magada, garden Kundina kingdom, and the kingdom Indraprasta and timescapes afternoon, seven in the evening, a full moon toward the fourth month, the afternoon before the evening and when the day was good. The characters in the Geguritan Hariwangsa namely Sang  Krishna,Dewi  Rukmini, Sang Jarasandha, Hyang Narada SangYudistira, Sang Arjuna, Sang Bima, Ni Kesari and I Priambada. Themes in kakawin hariwangsa is loyalty and mandate that we have to wait for someone to love us because no matter how hard we will unite separated. Kakawin Hariwangsa of narrative structure and Geguritan Hariwangsa obtained reception of kakawin towards geguritan where reception is not done thoroughly because there are some differences .